Marketplace credibility and online purchase decisions on Shopee: Evidence from banking professionals in Surabaya - Rakhmawati, Dewi (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This study examines the influence of marketplace quality and credibility on online purchase decisions among banking professionals using Shopee in Surabaya, Indonesia. In the era of digital transformation, the marketplace has become a critical determinant of consumer trust, particularly for professionals with limited time who rely on efficient and credible online platforms. Using a quantitative approach and Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 97 bank employees who had made at least one purchase via Shopee. The results indicate that marketplace quality significantly affects credibility, and both variables positively influence purchase decisions. Credibility also partially mediates the relationship between marketplace and purchase decision, suggesting that technological excellence alone is insufficient without the presence of perceived trustworthiness. The model explains 76% of the variance in purchase decisions, indicating substantial predictive power. These findings align with the Unified Theory of Acceptance and Use of Technology (UTAUT2) and the Integrated Trust–Technology Framework, emphasizing that convenience, transparency, and perceived reliability are central to digital consumer behavior. The study contributes to e-commerce and consumer trust literature by providing empirical evidence from an emerging economy context, highlighting the interplay between marketplace design and relational credibility. Practically, e-marketplace operators are encouraged to strengthen their platforms’ credibility through transparent seller verification, secure payment mechanisms, and consistent marketing communication to enhance user trust and loyalty. This research underscores the strategic role of credibility as a psychological bridge connecting marketplace performance with consumer commitment in digital purchasing